2001
DOI: 10.3102/00028312038002289
|View full text |Cite
|
Sign up to set email alerts
|

Policy Is Not Enough: Language and the Interpretation of State Standards

Abstract: Words have no inherent meaning. Instead, they signify ideas or actions ascribed to them by communities, and meanings for specific words often vary across those communities. Words that carry specialized meanings in one community can be interpreted differently by another, particularly where individuals in the second community have little access to dialogues in the first, or when forces in the second community compete to assign meaning to key words. Observations of one district's mathematics curriculum writing co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
141
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(146 citation statements)
references
References 15 publications
4
141
0
1
Order By: Relevance
“…Some researchers have found strong effects of policy alignment on teacher knowledge and beliefs and on teachers' classroom practice (Levitt, 2001;Swanson & Stevenson, 2002), but others have found only modest effects (Blank, Porter, & Smithson, 2001). A recurring theme in research that examines effects of policies on cognition is that local actors often misinterpret the intentions of policy makers (Hill, 2001;Spillane, 2004;Spillane & Callahan, 2002). As local actors interact with one another, moreover, they develop shared but local meanings of policies and curricular interventions that can proliferate misunderstandings of policy intentions (Reiser et al, 2000;Spillane, Diamond, Walker, Halverson, & Jita, 2001).…”
Section: Alignment As a Policy Instrument For Promoting Curriculum Immentioning
confidence: 99%
See 2 more Smart Citations
“…Some researchers have found strong effects of policy alignment on teacher knowledge and beliefs and on teachers' classroom practice (Levitt, 2001;Swanson & Stevenson, 2002), but others have found only modest effects (Blank, Porter, & Smithson, 2001). A recurring theme in research that examines effects of policies on cognition is that local actors often misinterpret the intentions of policy makers (Hill, 2001;Spillane, 2004;Spillane & Callahan, 2002). As local actors interact with one another, moreover, they develop shared but local meanings of policies and curricular interventions that can proliferate misunderstandings of policy intentions (Reiser et al, 2000;Spillane, Diamond, Walker, Halverson, & Jita, 2001).…”
Section: Alignment As a Policy Instrument For Promoting Curriculum Immentioning
confidence: 99%
“…Past studies have shown that prior knowledge affects teachers' interpretation of state standards, which are often limited in the guidance they provide to teachers for how to interpret them (Hill, 2001(Hill, , 2006L. K. Smith & Southerland, 2007).…”
Section: How People and Places Could Affect The Success Of Alignment mentioning
confidence: 99%
See 1 more Smart Citation
“…As Spillane notes (cited in Olson, 2001), school districts can "amplify, drown out, or minimize" the impact of standards in schools. In addition the language of standards is itself subject to interpretation (Hill, 2001). State articulation of desired content in no way guarantees that the language embedded in state documents will be interpreted by local educators in ways states intend.…”
Section: Introductionmentioning
confidence: 99%
“…Policy is therefore presented as an iterative process rather than linear progression from formulation to implementation and then evaluation. In other words, policy changes across settings and over time (Hill 2001;Lin 2000;Levinson and Sutton 2001;Spillane 2004). What has not been adequately explored is the fact that the understanding of policy changes over time even for one person or within one group.…”
Section: Temporalitymentioning
confidence: 99%